Diagnostic timing dependent characteristics of acute kidney injury following hepatectomy: a retrospective historical cohort analysis. Issue 12 (December 2021) - Mizunoya, Kazuyuki; Yagi, Yasunori; Kamachi, Hirofumi; Kamiyama, Toshiya; Morimoto, Yuji; Taketomi, Akinobu
Abstract: Background: The timing of diagnosis of post-hepatectomy acute kidney injury (AKI) has rarely been investigated. The aim of this retrospective study was to reveal the differences between AKI subtypes following hepatectomy, as classified by timing of diagnosis. Method: Post-hepatectomy AKI was classified as very transient AKI (vtAKI; criteria satisfied by the serum creatinine value immediately after surgery) or non-transient AKI (ntAKI; all other AKI types except for vtAKI). Multivariate logistic regression analyses for both AKI types were performed separately to identify differences in known perioperative AKI risk factors. The impacts of each AKI subtype on postoperative complications, hospital stay and renal outcome at discharge were also evaluated. Results: AKI was diagnosed in 135 of 750 patients (18.0%); 82 and 53 patients were classified as vtAKI and ntAKI, respectively. In multivariate analysis, even among the perioperative factors associated with whole AKI, there were distinct relationships depending on vtAKI or ntAKI. Furthermore, only ntAKI was associated with postoperative complications, longer hospital stays and impaired renal function at discharge. Conclusions: Based on the results of this study, future post-hepatectomy AKI studies should only include ntAKI and exclude vtAKI, as vtAKI has minimal clinical impact despite accounting for a significant proportion of AKI patients. Clinical trial registrations: None.